The development and validation of a novel LC–MS/MS method for the quantification of cenicriviroc in human plasma and cerebrospinal fluid. (20th November 2019) - Dilly Penchala, Sujan; Alagaratnam, Jasmini; Challenger, Elizabeth; Amara, Alieu; Else, Laura; Winston, Alan; Khoo, Saye
Abstract: A high‐performance liquid chromatography tandem mass spectrometric method was developed and validated for cenicriviroc (CVC) quantification in human plasma and cerebrospinal fluid (CSF). The method involved precipitation with acetonitrile and injecting supernatants onto the column. Separation was achieved on an XBridge C18 column with a gradient elution of 0.1% formic acid in water and acetonitrile. Analyte detection was conducted in positive ion mode using selected reaction monitoring. The m / z transitions were: CVC (697.3 → 574.3) and CVC‐d7 (704.4 → 574.3). Calibration curve ranged from 5 to 1000 ng/mL for plasma and from 0.241 to 15.0 ng/mL for CSF. The intra‐ and inter‐day precision and accuracy were <15% for both plasma and CSF across four different concentrations. CVC recovery from plasma and artificial CSF was >90%. The method was utilized for the measurement of patients' plasma and CSF samples taking a dose of 50, 150 and 300 mg q.d.